Value Risk Premium, Investor Sentiment and Stock Returns in Kenya. - Nebat Galo Mugenda; Tobias Olweny; Joshua M Wepukhulu (AFRE (Accounting and Financial Review), 2022)
AbstractThis study sought to investigate the role of investor sentiment in the relationship between value risk premium and stock returns in Kenya, controlling for effect of market, size, profitability and asset growth. The variables were anchored on postulations in the Dividend Valuation Model. The study utilized monthly time series data on 60 firms listed at the NSE from 2011-2019. The result of ADF and P-P tests indicated a mix of variables stationary at level and 1st difference. The F-bounds cointegration test revealed long-run relationship among variables thus requiring estimation of both ARDL and VEC models. Results show weak evidence for existence of value risk premium at the NSE using the main effects model. The pricing effect of value risk premium is however enhanced in the interaction model. The interaction though not significant implying that there is no moderating effect of sentiment. Investors can therefore strategically build up their portfolios to allocate more funds to high book-to-market equity stocks and earn relatively high returns regardless of the market condition. The study further recommends a pricing model that incorporates investor sentiment as additional source of systematic risk in cost of capital decisions at the NSE.DOI: https://doi.org/10.26905/afr.v5i3.6637